2022
DOI: 10.1371/journal.pone.0274846
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity levels and adherence to physical activity guidelines in people with multimorbidity—A systematic review and meta-analysis

Abstract: Objective To determine levels of objectively measured physical activity (PA) and the proportion of adults with multimorbidity that adheres to PA guidelines. Methods All studies, where PA was measured at baseline using an activity monitor in an adult (≥18 years) multimorbid (≥80% of the population had ≥2 chronic conditions) population. A systematic literature search was performed in Medline, EMBASE, CINAHL, CENTRAL, ClinicalTrials.gov, opengrey.eu and google.com from inception up until 18th of January 2022. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…A recent systematic review showed strong evidence of the positive impact of wearables on increasing physical activity among the general population, although effect on physiological and psychosocial measures was not clear [15]. Despite these findings, limited evidence exists on elderly patients with multimorbidity, both on objectively measured PA as well as on the efficacy of using activity trackers to improve PA [16]. Commercial offthe-shelf activity trackers allow users to self-monitor their daily PA, including the number of steps, type of PA, and amount of sleep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review showed strong evidence of the positive impact of wearables on increasing physical activity among the general population, although effect on physiological and psychosocial measures was not clear [15]. Despite these findings, limited evidence exists on elderly patients with multimorbidity, both on objectively measured PA as well as on the efficacy of using activity trackers to improve PA [16]. Commercial offthe-shelf activity trackers allow users to self-monitor their daily PA, including the number of steps, type of PA, and amount of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial offthe-shelf activity trackers allow users to self-monitor their daily PA, including the number of steps, type of PA, and amount of sleep. Fitbit (Fitbit Inc, San Francisco, CA, USA) activity trackers have previously been utilized as both measurement and intervention tools, however, it is unclear how they are being integrated into PA intervention studies, and their use in MM patients remains limited [16,17]. Moreover, in order to access the impact of the PA the patient's view must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…One of society's greatest challenges is to combat sedentary lifestyles in order to prevent the onset of cardiovascular diseases and problems associated with physical inactivity [1], since physical inactivity is considered the fourth leading risk factor for mortality worldwide [2]. Research has associated low or non-existent levels of physical activity with an increased risk of developing diseases such as diabetes, cardiovascular diseases, hypertension, breast or colon cancer, as well as mental illness [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed strong evidence of the positive impact of wearables on increasing physical activity among the general population, although effect on physiological and psychosocial measures was not clear [ 15 ]. Despite these findings, limited evidence exists on older adult patients with multimorbidity, both on objectively measured PA as well as on the efficacy of using activity trackers to improve PA [ 16 ]. Commercial off-the-shelf activity trackers allow users to self-monitor their daily PA, including the number of steps, type of PA, and amount of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial off-the-shelf activity trackers allow users to self-monitor their daily PA, including the number of steps, type of PA, and amount of sleep. Fitbit (Fitbit Inc, San Francisco, CA, USA) activity trackers have previously been utilized as both measurement and intervention tools, however, it is unclear how they are being integrated into PA intervention studies, and their use in Multimorbidity (MM) patients remains limited [ 16 , 17 ]. Moreover, in order to access the impact of the PA the patient’s view must be considered.…”
Section: Introductionmentioning
confidence: 99%